2021
DOI: 10.1111/jmg.12590
|View full text |Cite
|
Sign up to set email alerts
|

Th–U powered metamorphism: Thermal consequences of a chemical hotspot

Abstract: The Arkaroola region of the northern Flinders Ranges, South Australia, records high geothermal gradient mineral assemblages that are not spatially or temporally associated with intrusive magmatism. Cordierite-bearing schists from the base of a ~12 km thick Neoproterozoic sedimentary sequence known as the Adelaide Rift Complex directly overlie Mesoproterozoic metasedimentary and granitic rocks with regional heat production values of ~7.9 µW/m 3 at 580 Ma, two to three times greater than global average values fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 95 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…Depine et al, 2008). Alternatively, several authors argue that HTLP metamorphism is most effectively caused by protracted crustal reworking leading to selective enrichment in U, Th, K and other heat‐producing elements (Sandiford & McLaren, 2002; Gerdes et al, 2000; Rudnick & Gao, 2003; Jaupart & Marechal, 2007; Kumar et al, 2007; Lexa et al, 2011; De Vraies van Leeuwen et al, 2021). The last model has been demonstrated as an effective thermal source yielding to the development of orogen‐scale thermal anomalies that can persist over millions of years (Burg & Gerya, 2005; Nabelek et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Depine et al, 2008). Alternatively, several authors argue that HTLP metamorphism is most effectively caused by protracted crustal reworking leading to selective enrichment in U, Th, K and other heat‐producing elements (Sandiford & McLaren, 2002; Gerdes et al, 2000; Rudnick & Gao, 2003; Jaupart & Marechal, 2007; Kumar et al, 2007; Lexa et al, 2011; De Vraies van Leeuwen et al, 2021). The last model has been demonstrated as an effective thermal source yielding to the development of orogen‐scale thermal anomalies that can persist over millions of years (Burg & Gerya, 2005; Nabelek et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“… (a) Surface radiogenic heat production map of central Australia calculated at 250 Ma during the latter stages of Tasmanide deformation, following methodology of De Vries Van Leeuwen et al. (2021). Modern U, Th, and K abundances as determined by radiometric surveys (Minty et al., 2009, 2010) were extrapolated back in time based on respective isotopic decay constants to determine concentrations at 250 Ma, and transformed to radiogenic heat production using the expected heat production attributed to each element.…”
Section: Discussionmentioning
confidence: 99%
“…A first consideration is South Australia's enrichment in heat producing elements (HPE) which is shown to generate anomalously elevated geothermal gradients and heat flows across the region [83]. This has produced the South Australian Heat Flow Anomaly in which heat flow is two to three times above average and can drive high temperature-low pressure metamorphism (e.g., [83][84][85]). In the Yorke Peninsula, SE Gawler Craton, Bockmann et al [85] found evidence for a metamorphic event between 1.56-1.5 Ga, thermally driven by this HPE heat anomaly at P-T conditions of 660-750 • C and 3.6-5.5 kbar.…”
Section: Were All Microstructures Obliterated By Coupled Dissolution ...mentioning
confidence: 99%